Evaluation of genetic relationship within and between mice strains using microsatellite markers - Purohit, Nishtha; Kumar, Mahadeo; Srivastav, Anurag Kumar; Purohit, Dinesh Chandra Purohit (Research in Biotechnology, 2015)
Mouse is the most commonly used animal research model in biology with hundreds of established inbred, outbred, and transgenic strains. They are mammal sharing a high degree of homology with human and other non human primates. In current study to evaluate the genetic relationship between different strains of mice 5 samples of each 14 different strain of mice were used and tested for different 14 microsatellite markers. The analysis of data revealed that the observed number of alleles varied from 2 to 6 for the strains of mice between the strains. The Effective number of alleles was reported from 2.543-10.515 in overall experimental population. Shannon’s Index range from 1.218 to 2.459 show limited genetic variation. The observed homozygosity obtained ranges from 0.5143 to 8.571 at selected loci. The observed heterozygosity obtained ranges from 0.142 to 0.485. In case D1Mit16 loci showed maximum Polymorphic information content (PIC) values up to 0.4486 while minimum PIC value of 0.2923 using D1Mit356. The maximum expected average heterozygosity of inbred strain of mice was 0.2486 for D1Mit17whereas minimum of 0.0922 using D17Mit62. It is observed that different genetic sites in these strains are showing low genetic diversity and low selection potentials and therefore, may also act as genetic markers to find out the source of origin and contamination. However, it is suggested that in future this study should be conducted by testing more number of individuals and for greater number of microsatellite markers.